Interim methadone – Effective but underutilized: A scoping review. (1st August 2021) - McCarty, Dennis; Chan, Brian; Bougatsos, Christina; Grusing, Sara; Chou, Roger
Highlights: Interim methadone patients receive methadone while on a counseling waitlist. A scoping review assessed the evidence supporting interim methadone. During interim methadone, heroin use declines and patients are retained in care. Alternatives to interim methadone may provide more clinical flexibility. Greater use of interim methadone could enhance access to opioid agonist therapy. Abstract: Background: Opioid treatment programs (OTPs) may provide interim methadone services – up to 120 days of methadone dosing without counseling. Regulatory requirements limit use of interim methadone services. We summarized the evidence on interim methadone and other strategies to minimize wait lists in OTPs. Methods: A scoping review selected studies of interim methadone and strategies that facilitated access to methadone. Randomized trials and controlled observational studies were prioritized; if evidence was lacking, lesser quality evidence was included. Results: Six studies examined interim methadone and three studies examined alternatives: low threshold services, an open access policy, and a medication first policy. The studies included four randomized clinical trials of interim methadone (with three follow-up reports and five secondary analyses), one prospective cohort of interim methadone, one retrospective cohort of interim methadone, one randomized trial of low threshold services and two pre-post assessments of changes in program or state policies. The clinical trials and observational cohorts reported reductions in heroin use during interim methadone and participants were more likely to enter OTPs than those on wait lists. Retention rates in interim methadone were similar to patients in active treatment. Studies testing strategies to facilitate access to methadone were effective without interim methadone's restrictions. Conclusion: Interim methadone appears to be effective and safe compared to wait list controls and provided similar outcomes to standard services. Interim methadone could increase access to OTPs. More research is needed on the alternative approaches to facilitate access to medication with comparisons to wait list controls and assessment of patient outcomes.